Язвенная болезнь желудка и двенадцатиперстной кишки: выбор тактики при кровотечении - G. K. Zherlov; A. P. Koshel; V. M. Vorobiyov; Yu. D. Yermolayev (Бюллетень сибирской медицины, 2006)
Ulcerative gastroduodenal bleedings remain the actual problem of emergency surgery because of quite frequency and high mortality. The analysis of treatment results in 782 patients was conducted. There were 239 patients with gastric ulcers, 488 patients with duodenal ulcers, 37 patients with combined ulcers and 18 patients with bleeding peptic ulcers of gastroenteranastomosis. The choice of surgical policy was based on emergency fibrogastroscopy findings. According to these findings the locality and severity of bleeding were defined using J. Forrest scale. The treatment began in intensive care with obligatory endoscopic control "by the program". Emergency operations were performed in 5,9% cases and urgent operations were performed in 16.4% cases of all patients who suffered with bleeding. There were 21,7% patients with operative treatment in remote and planned order. Postoperative mortality was 3,8%. Postoperative complications were in 12,2% patients. There were consider that the treatment of ulcerative gastroduodenal bleedings should be based on the individual active and waiting policy concluding in somatic patient's condition, duration of ulcerative anamnesis, presence of gastroduodenal bleedings in the past, ulcer location, and bleeding intensity (using J. Forrest scale) and effectiveness of conservative hemostasis.